Structural and functional maturation of rat primary motor cortex layer V neurons - Benedetti, Bruno; Dannehl, Dominik; Janssen, Jan Maximilian; Thielemann, Corinna; Couillard-Després, Sébastien; Engelhardt, Maren (International journal of molecular sciences, 2020)
Rodent neocortical neurons undergo prominent postnatal development and maturation. The process is associated with structural and functional maturation of the axon initial segment (AIS), the site of action potential initiation. In this regard, cell size and optimal AIS length are interconnected. In sensory cortices, developmental onset of sensory input and consequent changes in network activity cause phasic AIS plasticity that can also control functional output. In non-sensory cortices, network input driving phasic events should be less prominent. We, therefore, explored the relationship between postnatal functional maturation and AIS maturation in principal neurons of the primary motor cortex layer V (M1LV), a non-sensory area of the rat brain. We hypothesized that a rather continuous process of AIS maturation and elongation would reflect cell growth, accompanied by progressive refinement of functional output properties. We found that, in the first two postnatal weeks, cell growth prompted substantial decline of neuronal input resistance, such that older neurons needed larger input current to reach rheobase and fire action potentials. In the same period, we observed the most prominent AIS elongation and significant maturation of functional output properties. Alternating phases of AIS plasticity did not occur, and changes in functional output properties were largely justified by AIS elongation. From the third postnatal week up to five months of age, cell growth, AIS elongation, and functional output maturation were marginal. Thus, AIS maturation in M1LV is a continuous process that attunes the functional output of pyramidal neurons and associates with early postnatal development to counterbalance increasing electrical leakage due to cell growth.
Gesehen am 15.12.2025